Regional anesthesia in ophthalmic surgery (overview of the problem) - Khodakovsky, M (Pain medicine, 2022)
The article is devoted to the optimization of anesthetic management using regional methods of anesthesia in ophthalmic surgery. Methods and techniques of anesthetic management provide a sufficient level of anesthetic protection. All variants of regional anesthesia (monocomponent and combined) are used in the ophthalmological clinic “Optimal” on the basis of the Department of Anesthesiology, Intensive Care and Emergency Medicine of National Pirogov Memorial Medical University, Vinnytsia.